Introduction to the special issue on English medium instruction: Areas of research needing urgent attention - Macaro , Ernesto; Rose , Heath (Studies in Second Language Learning and Teaching, 2023)
English medium instruction (EMI), both in higher and secondary education, is now a well-established field of education research and, indeed, many applied linguistics journals are publishing regularly on a variety of EMI topics. Recently, a new journal, Journal of English-Medium Instruction, has been established that is dedicated entirely to this area of academic enquiry. Recent years have also seen several special issues emerge on topics within EMI in journals such as Applied Linguistics Review (published advanced online), System (in 2023), and TESOL Quarterly (in 2018).